Evaluating the Clinical Characteristics and Ophthalmic Manifestations in Children and Adolescents with Acquired Demyelinating Disorders in China - Li, Si-Yuan; Peng, Chun-Xia; Zuo, Hua-Xin; Lin, Qi; Yu, Ji-Feng; Liu, Wen; Li, Li; Shi, Wei (British journal of hospital medicine (London, England : 2005), 2025)
Pediatric acquired demyelinating disorders (ADS) include various monophasic and recurrent inflammatory conditions of the central nervous system (CNS). Optic neuritis (ON) is a demyelinating disease primarily affecting the optic nerve axons due to autoimmune inflammation. To investigate the clinical characteristics, ophthalmic manifestations, laboratory test results, and prognostic indicators of Chinese children and adolescents with ADS. The clinical data of 57 patients with ADS treated in the Beijing Children's Hospital from March 2021 to December 2023, were retrospectively collected and analyzed. The primary outcomes include best-corrected visual acuity (BCVA) at onset, peripapillary retinal nerve fiber layers (RNFL) thickness, serum myelin oligodendrocyte glycoprotein (MOG) antibody level, aquaporin-4 (AQP4) antibody level, and final BCVA after hormone therapy. The analyses included 57 children and adolescents in the study, including 38 optic neuritis (ON), 12 neuromyelitis optica spectrum disorder (NMOSD), 5 acute disseminated encephalomyelitis (ADEM), and 2 multiple sclerosis (MS) patients. The median age of patients facing the initial attack of ON was 9 years (3-15 years), with 23 children and adolescents (40.4%) aged eight years or younger, and 37 patients (64.9%) were bilaterally affected. Half of the children and adolescents (15/30) were MOG-Ab seropositive, and 19.4% (6/31) were AQP4-Ab seropositive. Children and adolescents with NMOSD were more likely to have severe visual impairment at acute onset ( < 0.05), with 84.2% of them having low vision acuity (BCVA worse than 0.1), as compared with 64.9% in the ON group. The RNFL thickness of affected eye was thinner than unaffected eyes (median 72.0 μm vs. median 102.0 μm, < 0.05). Patients with NMOSD exhibited lower RNFL thickness across all measured sectors compared to those with ON. Significant differences were noted in the average RNFL and in each specific region of the retina, including the temporal RNFL, nasal RNFL, nasal superior RNFL, nasal inferior RNFL, temporal superior RNFL, and temporal inferior RNFL (all < 0.05). After the treatment with intravenous methylprednisolone, both patients with ON (52 eyes; 86.7%) or NMOSD (20 eyes; 90.9%) group had functional visual recovery (BCVA better or equal 0.4). This study shows that Chinese children and adolescents with ADS present distinctive clinical features, including earlier onset and more bilateral involvement. Furthermore, NMOSD patients experience more severe visual acuity impairment and thinner peripapillary RNFL. All children and adolescents of ON or NMOSD respond well to methylprednisolone treatment.